2015
DOI: 10.23937/2378-3419/2/3/1018
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Two-Stage PCR Method for Quality Amplification of Degenerate DNA

Abstract: Formalin-fixed, paraffin-embedded (FFPE) tissue banks are invaluable to cancer genetics and biomarker discovery. However, FFPE tissue-derived DNA is degenerate. As such, any PCR technique which will give adequate amplification of such DNA to enable downstream applications is important to the characterization of genetic biomarkers and to personalized medicine. The aim of this article is to describe a two-stage PCR method which efficiently amplifies degenerate FFPE tissue-derived DNA. Ampliconenriched templates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…(7,8) Recently, studies have found new isolation methods of exosomes from liquid biopsy samples (urine, serum, breast milk, and plasma of blood), (9,10) and several products have been developed to reduce time and cost, increase reproducibility between laboratories, and efficiently concentrate exosomes. (11)(12)(13)(14) However, because mouse models are associated with complications in collecting liquid biopsy samples, such as small sample volumes due to mouse size, there has not been much research on exosomes in this field. In particular, gene expression analysis using mRNA in exosomes has been difficult.…”
Section: Introductionmentioning
confidence: 99%
“…(7,8) Recently, studies have found new isolation methods of exosomes from liquid biopsy samples (urine, serum, breast milk, and plasma of blood), (9,10) and several products have been developed to reduce time and cost, increase reproducibility between laboratories, and efficiently concentrate exosomes. (11)(12)(13)(14) However, because mouse models are associated with complications in collecting liquid biopsy samples, such as small sample volumes due to mouse size, there has not been much research on exosomes in this field. In particular, gene expression analysis using mRNA in exosomes has been difficult.…”
Section: Introductionmentioning
confidence: 99%